ISOTRETINOIN AND INFLAMMATORY LOW BACK PAIN; BEWARE! - Koca, S. S.; Albayrak, F.; Kisacik, B. (Elsevier, 2024)
[Abstract Not Available]
Meeting of the European-Alliance-of-Associations-for-Rheumatology (EULAR) -- JUN 12-15, 2024 -- Vienna, AUSTRIA